Efficacy of Different Insecticides against Rice Leaf Folder (Cnaphalorosis medinalis) Under Field Conditions - Soomro, Abdul Samad; Mazari, Shabana Naz; Hulio, Muhammad Haroon; Soomro, Junaid Ahmed; Junejo, Ghulam Qadeer (International Journal of Applied Sciences and Biotechnology, 2020)
The experiment was conducted at the field of Rice Research Institute Dokri, Larkana, Pakistan to evaluate the efficacy of different insecticides against Rice Leaf folder (Cnaphalocrosis medinalis) under field conditions, different insecticides were applied on recommended dose. The experiment was conducted in RCBD design with 3 Replications and 5 Treatments. The leaf damage and insect pest population were observed before spray and 1,3,5,7 and 14 days respectively. The results shown that all the treated plots reduced damage minimized insect pest population and increased yield at significant level compare to control. Minimum damage of leaves was recorded in T-03 Belt 480SC (3.76%) leaves/Plant compare to T-05 Control (28.96%) leaves/plant. The results revealed that the 1st application reduced population at significant level up to seven days but population started rebuilding among all treated plots Maximum control was observed in T-03 Notice 0.22/Plant on 5-DAA & 0.24/Plant on 7-DAA. Similarly, the 2nd application also produced desirable results against Rice leaf folder population at significant level among all treated plots except control plots. Maximum controlled was observed in T-3 Belt 480SC, 0.24, 0.5 and 0.54/plant in 5-DAA, 7-DAA and 14-DAA respectively. Maximum yield increase in T-03 Belt 480SC (20.47%), followed by T-01 Notice (19.21). Results shown that the pest appearance the time of booting caused more damage to flag leave, at the time of flowering reduced gain filling and ultimately yield losses were observed.